2015
DOI: 10.1007/s00299-015-1889-3
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid (BR) biosynthetic gene lhdd10 controls late heading and plant height in rice (Oryza sativa L.)

Abstract: A Brd2 allele suppresses heading date by altering the expression of heading date regulators such as OsMADS50 , and also negatively regulates chlorophyll biosynthesis. Heading date and plant height are important determinants of yield in rice (Oryza sativa L.). In this study, we characterized a late heading, dwarf mutant known as lhdd10 selected following ethyl methane sulfonate (EMS)-treatment of ssp. indica cultivar 93-11. lhdd10 showed late heading, dwarfness and slightly darker-green leaves than wild-type 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…There are 4259 genes screened out and annotated by KEGG: Kyoto Encyclopedia of Genes and Genomes (http://www.genome.jp/kegg/), and there were 104 pathways having been annotated in total. The brassinosteroid regulation is a main pathway related to plant height as described previously (Clouse & Sasse, ; Liu et al., ; Nomura et al., ; Wang et al., ). The ko number of brassinosteroid regulation is ko00905, which is a subset of Ko04075, and Ko04075 is plant hormone signal transduction having a significant relationship with plant growth and development, especially on stem growth, as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 4259 genes screened out and annotated by KEGG: Kyoto Encyclopedia of Genes and Genomes (http://www.genome.jp/kegg/), and there were 104 pathways having been annotated in total. The brassinosteroid regulation is a main pathway related to plant height as described previously (Clouse & Sasse, ; Liu et al., ; Nomura et al., ; Wang et al., ). The ko number of brassinosteroid regulation is ko00905, which is a subset of Ko04075, and Ko04075 is plant hormone signal transduction having a significant relationship with plant growth and development, especially on stem growth, as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…A number of plant height genes have been identified in different crops; for instance, ph1 , lhdd10 and dwarf1 were detected in rice (Deng et al., ; Kovi et al., ; Liu et al., ); ZmGA3ox2 and a favourable allele for dwarfing on chromosome 5 (SNP PZE‐105115518) were detected in maize (Teng et al., ; Weng et al., ); cd1, Dt1 and GmBRI1 have been identified in soybean (Wang, Sun, Wu, Han, & Wang, ; Zhang, Zhang, Han, Zhang, & Yu, ; Zhang et al., ). Brassinosteroids are a group of plant steroid hormones that regulate plant growth and development; the pathways of brassinosteroids that have been identified in some research showed the significant relationship with plant height (Clouse & Sasse, ; Liu et al., ; Nomura et al., ; Wang et al., ). With the genome of soybean being sequenced, having access to the physical map will accelerate fine mapping and cloning (Schmutz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Glyma.11G087300 and Glyma.20G014300 were annotated as auxin efflux carrier family proteins, with pin1b (polar-localised auxin efflux protein) mutants having increased stem elongation in Brachypodium [42]. Glyma.13G052900 was annotated as brassinosteroid-6-oxidase 2; brassinosteroids are plant steroid hormones that promote stem elongation in a variety of plants such as soybean and rice [43,44]. These observations showed an indirect relationship with the NNMS.…”
Section: Gene Mining From Nnms Consensus Qtl Intervalsmentioning
confidence: 98%
“…These mutations intervene at multiple points in the synthetic pathway. For example, brd2 (Hong et al 2005) and lhdd10 (Liu et al 2016) are mutations in a gene orthologous to Arabidopsis DIMINUTO/DWARF1 (AtDIM/ DWF1) (Klahre et al 1998) that encodes a FAD-linked oxidoreductase that catalyzes the conversion of 24-methylene cholesterol to campesterol upstream of the committed BR pathway. Resultant plants are dark green semidwarfs with erect leaves and reduced fertility.…”
Section: Brassinosteroid Synthesismentioning
confidence: 99%